2022
DOI: 10.1159/000525656
|View full text |Cite
|
Sign up to set email alerts
|

Skin Treatment with Detergent Induces Dermatitis with H1-Antihistamine-Refractory Itch and Upregulates IL-4 and Th17/Th22 Cytokine Gene Expression in C57BL/6 Mice

Abstract: <b><i>Introduction:</i></b> Repeated skin contact to detergents causes chronic irritant contact dermatitis (ICD) associated with itch sensation and eczema. However, the mechanisms of detergent-induced ICD are poorly understood. Here, we established a new murine model of detergent-induced ICD with H1-antihistamine-refractory itch. <b><i>Methods:</i></b> Ear skin of wild-type and mast cell-deficient mice on the C57BL/6 genetic background was treated with a detergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Nonatopic healthcare workers had a significant TEWL increase after hand sanitizer use compared with nonatopic nonhealthcare workers ( P < 0.05), suggesting that healthcare workers have a compromised skin barrier from frequent hand hygiene. In mice, exposure to the cytotoxic ingredients in detergents caused increase in pro-inflammatory cytokines with increased TEWL [73 ▪ ] and skin inflammation with itch and upregulation of cytokines involved in allergic responses [74 ▪ ,75 ▪ ].…”
Section: Detergentsmentioning
confidence: 99%
“…Nonatopic healthcare workers had a significant TEWL increase after hand sanitizer use compared with nonatopic nonhealthcare workers ( P < 0.05), suggesting that healthcare workers have a compromised skin barrier from frequent hand hygiene. In mice, exposure to the cytotoxic ingredients in detergents caused increase in pro-inflammatory cytokines with increased TEWL [73 ▪ ] and skin inflammation with itch and upregulation of cytokines involved in allergic responses [74 ▪ ,75 ▪ ].…”
Section: Detergentsmentioning
confidence: 99%
“…Interesting, very recently, Masutani and collaborators showed that detergents including sodium dodecyl sulphate induce mast cell-independent skin inflammation with H1-antihistamine-refractory itch in mouse skin [16].…”
Section: Introductionmentioning
confidence: 99%